Psychiatric and Behavioral Complications of GPi DBS in an Adolescent with Myoclonus Dystonia - Kriegel, Graciela; Stuckey, Melanie I. (Case Reports in Psychiatry, 2019)
Myoclonus dystonia is a rare movement disorder that often causes significant disability. Deep brain stimulation of the internal pallidum (GPi DBS) is a recommended treatment for those who do not respond to pharmacotherapy or who have intolerable side effects. This paper reports on the case of a 17-year-old male who was admitted to a tertiary level mental healthcare facility for treatment of psychiatric and behavioral symptoms thought to be related to GPi DBS. Prior to GPi DBS insertion, the patient was diagnosed with anxiety and mild obsessive compulsive disorder (OCD). Following insertion, his OCD became severe and he developed depression, Tourette syndrome, and stuttering. His first admission to a psychiatric unit was for management of a manic episode following treatment for depression with fluoxetine, and he began to exhibit severe aggressive behavior. GPi DBS was turned off, but there were neither changes in dystonic movements nor improvement in aggressive behavior or psychiatric symptoms, though stuttering improved. The patient was transferred to a secure treatment centre where he was able to gain control over his behaviors with intense dialectical behavior therapy, but the aggressive behavior and safety concerns continue to persist today.